The Wild Mouse (Micromys minutus): Reservoir of a Novel Campylobacter jejuni Strain - Kim, Junhyung; Guk, Jae-Ho; Mun, Seung-Hyun; An, Jae-Uk; Kim, Woohyun; Lee, Soomin; Song, Hyokeun; Seong, Je Kyung; Suh, Jun Gyo; Cho, Seongbeom (Frontiers in Microbiology, 2020)
Campylobacter jejuni is one of the most common zoonotic pathogens worldwide. Although the main sources of human C. jejuni infection are livestock, wildlife can also affect C. jejuni transmission in humans. However, it remains unclear whether wild mice harbor C. jejuni and are involved in the ‘environment–wildlife–livestock–human’ transmission cycle of C. jejuni in humans. Here, we characterized C. jejuni from wild mice and identified genetic traces of wild mouse-derived C. jejuni in other hosts using a traditional approach, along with comparative genomics. We captured 115 wild mice (49 Mus musculus and 66 Micromys minutus) without any clinical symptoms from 22 sesame fields in Korea over 2 years. Among them, Micromys minutus were typically caught in remote areas of human houses and C. jejuni was solely isolated from Micromys minutus (42/66, 63.6%). We identified a single clone (MLST ST-8388) in all 42 C. jejuni isolates, which had not been previously reported, and all isolates had the same virulence/survival-factor profile, except for the plasmid-mediated virB11 gene. No isolates exhibited antibiotic resistance, either in phenotypic and genetic terms. Comparative-genomic analysis and MST revealed that C. jejuni derived from Micromys minutus (strain SCJK2) was not genetically related to those derived from other sources (registered in the NCBI genome database and PubMLST database). Therefore, we hypothesize that C. jejuni from Micromys minutus is a normal component of the gut flora following adaptation to the gastro-intestinal tract. Furthermore, Micromys minutus-derived C. jejuni had different ancestral lineages from those derived from other sources, and there was a low chance of C. jejuni transmission from Micromys minutus to humans/livestock because of their habitat. In conclusion, Micromys minutus may be a potential reservoir for a novel C. jejuni, which is genetically different from those of other sources, but may not be involved in the transmission of C. jejuni to other hosts, including humans and livestock. This study could form the basis for further studies focused on understanding the transmission cycle of C. jejuni, as well as other zoonotic pathogens originating from wild mice.